2022
DOI: 10.1590/s1677-5538.ibju.2022.0313
|View full text |Cite
|
Sign up to set email alerts
|

Enuresis and upper airway obstruction: BNP and ADH hormones behavior before and after airway surgery

Abstract: Introduction: Upper airway obstruction (UAO) is a common condition in all pediatric population, with a 27% prevalence. Primary monosymptomatic nocturnal enuresis (PMNE) is a condition related to UAO in 8% to 47% of these children. The specific pathophysiological mechanism of this bond is not well understood. Some authors suggest a connection between brain natrituretic peptide (BNP) and anti-diuretic hormone (ADH) during sleep. The aim of this study was to evaluate hormone profile (ADH and BNP) and improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The improvement shown for nocturnal enuresis in the study by Ribeiro et al ( 5 ) was clinically very large (d=1.50) compared to the effects of surgery on the concentration of ADH (d=0.38) and BNP (d=0, 32), which are considered small clinical effects, even the comparison before and after BNP being significant from the probabilistic point of view.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The improvement shown for nocturnal enuresis in the study by Ribeiro et al ( 5 ) was clinically very large (d=1.50) compared to the effects of surgery on the concentration of ADH (d=0.38) and BNP (d=0, 32), which are considered small clinical effects, even the comparison before and after BNP being significant from the probabilistic point of view.…”
mentioning
confidence: 84%
“…The study by Ribeiro et al ( 5 ), published in this journal in issue 48 ( 6 ), presents interesting results on enuresis. However, we bring an analysis based on clinical effect measurement to complement the probabilistic analysis presented by the authors.…”
mentioning
confidence: 89%
“…The association between enuresis and SDB has already been demonstrated in several studies (6)(7)(8)(9). Various studies have shown resolution of two thirds or more of the cases of enuresis following surgical resolution of SDB through an adenoidectomy, with or without tonsillectomy (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 93%
“…In addition, partial or complete UAO events in SDB, micro-recurrent awakenings caused by obstruction of the upper airways lead to an increased threshold of awakening and stimulation such as bladder filling or contractions of the detrusor muscle become ineffective. ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The exact etiology of enuresis is not yet fully understood. It is considered multifactorial (1,2,(6)(7)(8)(9)(10)(11). One of the main factors involved in the pathophysiology of enuresis are hereditary factors (1,2,(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%